FAKTOR-FAKTOR YANG MEMENGARUHI PASANGAN USIA SUBUR MENJADI AKSEPTOR KB DI KELURAHAN BABURA KECAMATAN MEDAN SUNGGAL KOTA MEDAN TAHUN 2012 - Afni Andini; Asfriyati .; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
There are many efforts have been taken by the government to controlling population growth and improving human resources. One of the efforts is through by Family Planning programs that oriented to Small Family Norm Happy Prosperous. Although the Family Planning program in Indonesia stated quite successful, but the implementation is still a lot of couples of childbearing age who do not use contraceptives. The factors affecting couples of childbearing age become Family Planning acceptors such as, educational factor, knowledge factor, parity factor and cultural (belief) factor. This research aims to determine the factors that affect couples of childbearing age become acceptors of Family Planning based on education, knowledge, parity and cultural (belief) in (Sub-urban of Babura, Sub-district of Medan Sunggal, Medan of 2012). This research is descriptive-analytical by processing the data that distributed to the respondents by population in couples of childbearing age as an acceptor. The sampling was taken by Purposive Sampling with a large of sample of 62 in couples of childbearing age. The data was tested by Chi Square test with α 0,05. The results of research showed that higher levels of education is (72,6%), low knowledge level is (54,8%), parity of > 2 childs is (91,9%) and culture (belief) negative is (93,5%). The results of bivariate analysis showed there was no correlation between education and parity with couples of childbearing age become acceptors of Family Planning. But there is a correlation between knowledge and cultural (belief) with couples of childbearing age become acceptors of Family Planning. It is expected that family planning officials in sub-urban area to be more pro-active in providing outreach to the public especially for couples of childbearing age in order for them to better understand and comprehend the benefits of Family Planning and may change the paradigm of the values (belief) that exist in the community of public Keywords: The Factors Affecting Couples of Childbearing Age, Acceptors of Family Planning